ANALISA DAN PERANCANGAN SISTEM INFORMASI PENGENDALIAN PRODUKSI PADA PT TRIFOLI KAYAKARYA - Beby Tiara; Gusti Nyoman Budiadnyana; Aminul Fitri (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2016)
ABSTRACT : This research aims to control and plan the production process at thecompany. Production control at each company is very stressed, given the company''sdevelopment is strongly influenced by the smooth delivery of the goods on custemer, andof course the smooth delivery is highly depended on the planning process of production,so that good control is needed.Object of this research is PT. Trifoli kaya karya. Methodology The study was conductedin several ways including through interviews and observations. Interviews wereconducted between writer and part production planning manager. while the observationis a direct observation of all these aspects of the research.keywords: information systems, production, control